KAJIAN YURIDIS AKTA PERDAMAIAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG KOPERASI SIMPAN PINJAM INTIDANA (Kajian Terhadap Putusan Pengadilan Niaga Semarang Nomor: 10/Pdt.Sus-PKPU/2015/PN Niaga Smg) - Teddy Hartanto (MIH Unsoed, 2018)
This research intended to learn how the law consideration of Trade Court Judge Semarang Nimber 10/Pdt.Sus-PKPU/2015/PN.Niaga Smg that decided the Cancelation of Debt Payment Obligation of KSP Intidana that related to the conciliation plan? And how the impact of law for the KSP Creditor Intidana that didn”t agree with the conciliation statement decision in concelation of the Debt Payment Obligation by the Trade Court Semarang?The case that were researched it was the Trade Court Decision Semarang Number 10/Pdt.Sus-PKPU/2015/PN Niaga Smg and the documents related with . Beside thet the research was conducted with the literature research.Based on the data analysis of research result could be concluded that the Judge Decision didn”t consider the Article 231 (b) Ordinance Number 37 in 2004 about the Bankrupt and cancelation of Debt Payment Obligation in deciding the Creditor Committee. They could not represent the creditor entirely. Based on the Article 123 (1) HIR that could represent the creditor was advocate and Article 1795 Criminal Code of Civil Case, to represent one certain interest had to be given the specific power by creditor. The creditors that didn”t agree with the conciliation decision of the obligation cancelation of debt Payment they could do the law effort to propose the review to this decision or propose the concelation to the conciliation document because there was a mistake about the person or case.